Padrões de distribuição e organização trófica da assembleia de peixes no estuário do Rio Mamanguape, Paraíba, Brasil - Medeiros, Aline Paiva Morais de (2016)
The present study aimed to characterize a fish assemblage along a mangrove-reef gradient at Barra do Rio Mamanguape Environmental Protected Area, Paraíba, Brazil, according to the following parameters: spatial distribution, habitat use, feeding ecology and trophic guilds. This dissertation is divided in two chapters: the first one aims to describe the spatial and seasonal distribution, habitat use and ontogenetic shifts on estuary usage; the second one registers fish diet according to region, season and size classes of most abundant species as well as the trophic. Fish samples were gathered using three types of nets along seventeen sites, grouped in four regions according to salinity range: Reefs, Low, Middle and Upper estuaries. Most abundant species were Atherinela brasiliensis and Sphoeroides testudineus. Among the guilds, piscivores were the most abundant, followed by crab eaters. Herbivores were found with higher abundance in reefs. We registered differences in guilds distribution along the mangrove-reef gradient and according to seasons (dry and rainy). Caranx latus, Oligoplites palometa and Mugil curema occupied different regions in different life stages. We registered differences in guilds distribution along the mangrove-reef gradient and according to seasons (dry and rainy).